Bioinformatics analysis of the microRNA-mRNA network in sebaceous gland carcinoma of the eyelid - Hirano, Tetsushi (Mol Med Rep, 2021)
Sebaceous gland carcinoma (SGC) of the eyelid is an uncommon aggressive tumor with a relatively high rate of local recurrence and a poor prognosis following metastasis. However, the molecular mechanisms underlying the pathogenesis of SGC remain unclear. The purpose of the present study was to clarify microRNA (miRNA) expression profiles in SGC and to explore novel miRNA-mRNA networks of SGC. A small RNA-sequencing analysis was performed to identify miRNAs differentially expressed between SGC and sebaceous adenoma control samples. Bioinformatics analyses were conducted to reveal biological functions, canonical pathways and molecular interaction networks using integrated miRNA-mRNA datasets, including mRNA expression profiles of SGC from our previous study. The present results demonstrated that 16 upregulated miRNAs and 516 downregulated mRNAs were associated with loss of lipid metabolism function and enriched in cholesterol biosynthesis pathways. By contrast, 29 downregulated miRNAs and 194 upregulated mRNAs were mainly associated with the promotion of cell survival and proliferation in addition to enrichment of DNA damage-induced cell cycle-regulation pathways. Furthermore, network analyses revealed that the upregulated miRNAs, miR-130a-3p and miR-939-5p, and the downregulated miRNAs, miR-146a-5p, miR-149-3p, miR-193a-3p, miR-195-5p and miR-4671-3p, could be upstream regulators related to these functional changes of SGC. These results improved the understanding of molecular mechanisms of SGC and may help to improve the diagnosis of SGC.